Typenrevision der europäischen Arten der Gattung Diadegma Foerster (syn. Angitia Holmgren) (Hymenoptera: Ichneumonidae). - Horstmann, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Though the genus Diadegma Foerster (syn. Angitia Holmgren) contained some frequent species that were important for applied entomology, it had not been sufficiently examined for 80 years. To get sound foundations for a new systematization, it was necessary to revise to types of almost all the European species. Of approximately 118 species hitherto classified with this genus or its nearest relations, 27 species (including synonyms) do not belong there, 25 species are synonymous with other Diadegma species (4 of them are doubtful) and 4 cannot be determined because the types are missing or only a few males are known. On the other hand, 13 species are given new names; either they were wrongly identified with previously described species or they are new. In the case of six other species it was decided for the present not to attempt a new description. A key and brief descriptions are given for 82 species.Nomenclatural Actsanalis Pfankuch, 1914 (Angitia), syn. n. of Diadegma (Nythobia) maculata (Gravenhorst, 1829)antennalis Szépligeti, 1916 (Angitia), Lectotypeclaripennis Thomson, 1887 (Angitia), syn. n. of Diadegma (Nythobia) majalis (Gravenhorst, 1829)coleophorarum Ratzeburg, 1852, sensu Thomson, 1887 (Angitia), Neotype now a synonym of Diadegma (Neoangitia) coleophorarum (Ratzeburg, 1852)novakii Strobl, 1904 (Angitia), Lectotypepolyzona Thomson, 1887 (Angitia), syn. n. of Diadegma (Nythobia) maculata (Gravenhorst, 1829)pseudocombinata Szépligeti, 1916 (Angitia), Lectotype; syn. n. of Diadegma (Nythobia) armillata (Gravenhorst, 1829)pusilla Szépligeti, 1916 (Angitia), Lectotypusrimator Thomson, 1887 (Angitia), syn. n. of Diadegma (Nythobia) ruficeps (Holmgren, 1860)sprengeli Habermehl, 1935 (Angitia), syn. n. of Lathrostizus macrostoma (Thomson, 1887gigantea Szépligeti, 1916 (Angitia (Dioctes)), Lectotype now a synonym of Diadegma (Nythobia) terebrans (Gravenhorst, 1829)cerophagus Gravenhorst, 1829 (Campoplex), Lectotype; syn. n. of Omorga picticrus Thomson, 1887exareolatus Ratzeburg, 1852 (Campoplex), syn. n. of Diadegma (Nythobia) apostata (Gravenhorst, 1829)tibialis Gravenhorst, 1929 (Campoplex), Lectotype; syn. n. of Diadegma (Nythobia) armillata (Gravenhorst, 1829)vestigialis Ratzeburg, 1852 (Campoplex), syn. n. of Lathrostizus lugens (Gravenhorst, 1829)elachistae Brischke, 1880 (Cymodusa), syn. n. of Meloboris alternans (Gravenhorst, 1829)Neoangitia Horstmann, 1969 (Diadegma), sgen. n.baltica Horstmann, 1969 (Diadegma (Diadegma)), spec. n.litoralis (Holmgren, 1856) (Diadegma (Diadegma)), Lectotype described as Campoplex litoralisstagnalis (Holmgren, 1856) (Diadegma (Diadegma)), Lectotype described as Campoplex stagnalisangitiaeforma Horstmann, 1969 (Diadegma (Neoangitia)), spec. n.elongata (Thomson, 1887) (Diadegma (Neoangitia)), Lectotype described as Angitia elongatamajor (Szépligeti, 1916) (Diadegma (Neoangitia)), Lectotype described as Angitia majoraculeata (Bridgman, 1889) (Diadegma (Nythobia)), Lectotype described as Limneria (Angitia) aculeataanthracostoma (Strobl, 1904) (Diadegma (Nythobia)), Lectotype described as Angitia anthracostomabrevipetiolata Horstmann, 1969 (Diadegma (Nythobia)), spec. n.brevivalvis (Thomson, 1887) (Diadegma (Nythobia)), Lectotype described as Angitia brevivalviscrassa (Bridgman, 1889) (Diadegma (Nythobia)), Lectotype described as Limneria (Angitia) crassaelishae (Bridgman, 1884) (Diadegma (Nythobia)), Lectotype described as Limneria elishaeerucator (Zetterstedt, 1838) (Diadegma (Nythobia)), Lectotype described as Porizon erucatoreucerophaga Horstmann, 1969 (Diadegma (Nythobia)), spec. n.laricinella (Strobl, 1904) (Diadegma (Nythobia)), Lectotype described as Angitia laricinellaledicola Horstmann, 1969 (Diadegma (Nythobia)), spec. n.lithocolletis Horstmann, 1969 (Diadegma (Nythobia)), spec. n.longicaudata Horstmann, 1969 (Diadegma (Nythobia)), spec. n.melania (Thomson, 1887) (Diadegma (Nythobia)), Lectotype described as Angitia melaniamonilicornis (Thomson, 1887) (Diadegma (Nythobia)), Lectotype described as Angitia monilicornisneoapostata Horstmann, 1969 (Diadegma (Nythobia)), spec. n.neocerophaga Horstmann, 1969 (Diadegma (Nythobia)), spec. n.neomajalis Horstmann, 1969 (Diadegma (Nythobia)), spec. n.nervosae Horstmann, 1969 (Diadegma (Nythobia)), spec. n.nigrostigmatica Horstmann, 1969 (Diadegma (Nythobia)), spec. n.paludis Horstmann, 1969 (Diadegma (Nythobia)), spec. n.ruficeps (Holmgren, 1860) (Diadegma (Nythobia)), Lectotype described as Limneria ruficepsscotiae (Bridgman, 1889) (Diadegma (Nythobia)), Lectotype described as Limneria (Angitia) scotiaetenuipes (Thomson, 1887) (Diadegma (Nythobia)), Lectotype described as Angitia tenuipestransversalis (Szépligeti, 1916) (Diadegma (Nythobia)), Lectotype described as Angitia transversalisvariegata (Szépligeti, 1916) (Diadegma (Nythobia)), Lectotype described as Angitia variegatapolitor Aubert, 1960 (Horogenes), syn. n. of Diadegma (Nythobia) aculeata (Bridgman, 1889)puncticeps (Thomson, 1887) (Lathristizus), Lectotype described as Angitia puncticepsflexicauda Holmgren, 1860 (Limneria), syn. n. of Lathrostizus lugens (Gravenhorst, 1829)hydropota Holmgren, 1860 (Limneria), Lectotype; syn. n. of Diadegma (Diadegma) grisescens (Gravenhorst, 1829)reticulata Bridgman, 1884 (Limneria), Lectotype; syn. n. of Diadegma (Nythobia) apostata (Gravenhorst, 1829)ruficornis Bridgman, 1884 (Limneria), syn. n. of Meloboris alternans (Gravenhorst, 1829)volubilis Holmgren, 1860 (Limneria), Lectotypeannulipes Bridgman, 1889 (Limneria (Angitia)), syn. n. of Diadegma (Nythobia) pusio (Holmgren, 1860)ischnocera Thomson, 1887 (Meloboris), Lectotype; syn. n. of Diadegma (Diadegma) hygrobia (Thomson, 1887)